Extended iron phthalocyanine islands self-assembled on a Ge(001):H surface - Zuzak, Rafal; Szymonski, Marek; Godlewski, Szymon (Beilstein Journal of Nanotechnology, 2021)
Self-assembly of iron(II) phthalocyanine (FePc) molecules on a Ge(001):H surface results in monolayer islands extending over hundreds of nanometers and comprising upright-oriented entities. Scanning tunneling spectroscopy reveals a transport gap of 2.70 eV in agreement with other reports regarding isolated FePc molecules. Detailed analysis of single FePc molecules trapped at surface defects indicates that the molecules stay intact upon adsorption and can be manipulated away from surface defects onto a perfectly hydrogenated surface. This allows for their isolation from the germanium surface.
Keywords: hydrogenated semiconductor; iron phthalocyanine (FePc); scanning tunneling microscopy; self-assembly

(untitled) - Gross, L.; Mohn, F.; Moll, N.; Liljeroth, P.; Meyer, G. (Science, 2009)

(untitled) - Binnig, G.; Rohrer, H.; Gerber, C.; Weibel, E. (Phys. Rev. Lett., 1982)

(untitled) - Binnig, G.; Rohrer, H. (Surf. Sci., 1983)

(untitled) - Yousofnejad, A.; Reecht, G.; Krane, N.; Lotze, C.; Franke, K. J. (Beilstein J. Nanotechnol., 2020)

(untitled) - Lu, X.; Grobis, M.; Khoo, K. H.; Louie, S. G.; Crommie, M. F. (Phys. Rev. B, 2004)

(untitled) - Thygesen, K. S.; Rubio, A. (Phys. Rev. Lett., 2009)

(untitled) - Zuzak, R.; Dorel, R.; Krawiec, M.; Such, B.; Kolmer, M.; Szymonski, M.; Echavarren, A. M.; Godlewski, S. (ACS Nano, 2017)

(untitled) - Gross, L.; Moll, N.; Mohn, F.; Curioni, A.; Meyer, G.; Hanke, F.; Persson, M. (Phys. Rev. Lett., 2011)

(untitled) - Repp, J.; Meyer, G.; Stojković, S. M.; Gourdon, A.; Joachim, C. (Phys. Rev. Lett., 2005)

(untitled) - Schulz, F.; Drost, R.; Hämäläinen, S. K.; Liljeroth, P. (ACS Nano, 2013)

(untitled) - Koslowski, S.; Rosenblatt, D.; Kabakchiev, A.; Kuhnke, K.; Kern, K.; Schlickum, U. (Beilstein J. Nanotechnol., 2017)

(untitled) - Godlewski, S.; Goryl, G.; Kolodziej, J. J.; Szymonski, M. (Appl. Surf. Sci., 2010)

(untitled) - Naitoh, Y.; Rosei, F.; Gourdon, A.; Lægsgaard, E.; Stensgaard, I.; Joachim, C.; Besenbacher, F. (J. Phys. Chem. C, 2008)

(untitled) - Hirjibehedin, C. F.; Lutz, C. P.; Heinrich, A. J. (Science, 2006)

(untitled) - Palmgren, P.; Yu, S.; Hennies, F.; Nilson, K.; Åkermark, B.; Göthelid, M. (J. Chem. Phys., 2008)

(untitled) - Riss, A.; Wickenburg, S.; Tan, L. Z.; Tsai, H.-Z.; Kim, Y.; Lu, J.; Bradley, A. J.; Ugeda, M. M.; Meaker, K. L.; Watanabe, K.; Taniguchi, T.; Zettl, A.; et al. (ACS Nano, 2014)

(untitled) - de la Torre, B.; Švec, M.; Hapala, P.; Redondo, J.; Krejčí, O.; Lo, R.; Manna, D.; Sarmah, A.; Nachtigallová, D.; Tuček, J.; Błoński, P.; Otyepka, M.; et al. (Nat. Commun., 2018)

(untitled) - Pörtner, M.; Wei, Y.; Riss, A.; Seufert, K.; Garnica, M.; Barth, J. V.; Seitsonen, A. P.; Diekhöner, L.; Auwärter, W. (Adv. Mater. (Weinheim, Ger.), 2020)

(untitled) - Deimel, P. S.; Feulner, P.; Barth, J. V.; Allegretti, F. (Phys. Chem. Chem. Phys., 2019)

(untitled) - Reecht, G.; Krane, N.; Lotze, C.; Zhang, L.; Briseno, A. L.; Franke, K. J. (Phys. Rev. Lett., 2020)

(untitled) - Krane, N.; Lotze, C.; Reecht, G.; Zhang, L.; Briseno, A. L.; Franke, K. J. (ACS Nano, 2018)

(untitled) - Croshaw, J.; Dienel, T.; Huff, T.; Wolkow, R. (Beilstein J. Nanotechnol., 2020)

(untitled) - Bellec, A.; Ample, F.; Riedel, D.; Dujardin, G.; Joachim, C. (Nano Lett., 2009)

(untitled) - Gruyters, M.; Pingel, T.; Gopakumar, T. G.; Néel, N.; Schütt, C.; Köhler, F.; Herges, R.; Berndt, R. (J. Phys. Chem. C, 2012)

(untitled) - Godlewski, S.; Kolmer, M.; Kawai, H.; Such, B.; Zuzak, R.; Saeys, M.; de Mendoza, P.; Echavarren, A. M.; Joachim, C.; Szymonski, M. (ACS Nano, 2013)

(untitled) - Olszowski, P.; Zapotoczny, B.; Prauzner-Bechcicki, J. S.; Vilas-Varela, M.; Pérez, D.; Guitián, E.; Peña, D.; Szymonski, M. (J. Phys. Chem. C, 2015)

(untitled) - Ahmad Zebari, A. A.; Kolmer, M.; Prauzner-Bechcicki, J. S. (Beilstein J. Nanotechnol., 2013)

(untitled) - Engelund, M.; Papior, N.; Brandimarte, P.; Frederiksen, T.; Garcia-Lekue, A.; Sánchez-Portal, D. (J. Phys. Chem. C, 2016)

(untitled) - Gruyters, M.; Pingel, T.; Berndt, R. (Phys. Rev. B, 2013)

(untitled) - Godlewski, S.; Kawai, H.; Kolmer, M.; Zuzak, R.; Echavarren, A. M.; Joachim, C.; Szymonski, M.; Saeys, M. (ACS Nano, 2016)

(untitled) - Baseer Haider, M.; Pitters, J. L.; DiLabio, G. A.; Livadaru, L.; Mutus, J. Y.; Wolkow, R. A. (Phys. Rev. Lett., 2009)

(untitled) - Wyrick, J.; Wang, X.; Namboodiri, P.; Schmucker, S. W.; Kashid, R. V.; Silver, R. M. (Nano Lett., 2018)

(untitled) - Kolmer, M.; Zuzak, R.; Dridi, G.; Godlewski, S.; Joachim, C.; Szymonski, M. (Nanoscale, 2015)

(untitled) - Godlewski, S.; Kawai, H.; Engelund, M.; Kolmer, M.; Zuzak, R.; Garcia-Lekue, A.; Novell-Leruth, G.; Echavarren, A. M.; Sanchez-Portal, D.; Joachim, C.; Saeys, M. (Phys. Chem. Chem. Phys., 2016)

(untitled) - Godlewski, S.; Engelund, M.; Peña, D.; Zuzak, R.; Kawai, H.; Kolmer, M.; Caeiro, J.; Guitián, E.; Vollhardt, K. P. C.; Sánchez-Portal, D.; Szymonski, M.; Pérez, D. (Phys. Chem. Chem. Phys., 2018)

(untitled) - Ahmad Zebari, A. A.; Kolmer, M.; Prauzner-Bechcicki, J. S. (Appl. Surf. Sci., 2015)

(untitled) - Chen, Q.; Rada, T.; Bitzer, T.; Richardson, N. V. (Surf. Sci., 2003)

(untitled) - Sazaki, G.; Fujino, T.; Sadowski, J. T.; Usami, N.; Ujihara, T.; Fujiwara, K.; Takahashi, Y.; Matsubara, E.; Sakurai, T.; Nakajima, K. (J. Cryst. Growth, 2004)

(untitled) - Vaurette, F.; Nys, J. P.; Grandidier, B.; Priester, C.; Stievenard, D. (Phys. Rev. B, 2007)

(untitled) - Nakamura, M.; Matsunobe, T.; Tokumoto, H. (J. Appl. Phys., 2001)

(untitled) - Zeis, R.; Siegrist, T.; Kloc, C. (Appl. Phys. Lett., 2005)

(untitled) - Cheng, Z.; Du, S.; Guo, W.; Gao, L.; Deng, Z.; Jiang, N.; Guo, H.; Tang, H.; Gao, H.-J. (Nano Res., 2011)

(untitled) - Komeda, T.; Isshiki, H.; Liu, J. (Sci. Technol. Adv. Mater., 2010)

(untitled) - Wang, X.; Cai, Z.-F.; Wang, Y.-Q.; Feng, Y.-C.; Yan, H.-J.; Wang, D.; Wan, L.-J. (Angew. Chem., Int. Ed., 2020)

(untitled) - Lu, X.; Hipps, K. W. (J. Phys. Chem. B, 1997)

(untitled) - Fan, Q.; Luy, J.-N.; Liebold, M.; Greulich, K.; Zugermeier, M.; Sundermeyer, J.; Tonner, R.; Gottfried, J. M. (Nat. Commun., 2019)

(untitled) - Lu, X.; Hipps, K. W.; Wang, X. D.; Mazur, U. (J. Am. Chem. Soc., 1996)

(untitled) - Wang, Y.; Wu, K.; Kröger, J.; Berndt, R. (AIP Adv., 2012)

(untitled) - Sk, R.; Deshpande, A. (Mol. Syst. Des. Eng., 2019)

(untitled) - Bouju, X.; Mattioli, C.; Franc, G.; Pujol, A.; Gourdon, A. (Chem. Rev., 2017)

(untitled) - Goiri, E.; Borghetti, P.; El-Sayed, A.; Ortega, J. E.; de Oteyza, D. G. (Adv. Mater. (Weinheim, Ger.), 2016)

(untitled) - Gottfried, J. M. (Surf. Sci. Rep., 2015)

(untitled) - Bao, D.-L.; Zhang, Y.-Y.; Du, S.; Pantelides, S. T.; Gao, H.-J. (J. Phys. Chem. C, 2018)

(untitled) - Snezhkova, O.; Bischoff, F.; He, Y.; Wiengarten, A.; Chaudhary, S.; Johansson, N.; Schulte, K.; Knudsen, J.; Barth, J. V.; Seufert, K.; Auwärter, W.; Schnadt, J. (J. Chem. Phys., 2016)

(untitled) - Barth, J. V. (Annu. Rev. Phys. Chem., 2007)

(untitled) - Sabik, A.; Mazur, P.; Gołek, F.; Trembulowicz, A.; Antczak, G. (J. Chem. Phys., 2018)

(untitled) - Tang, C. W. (Appl. Phys. Lett., 1986)

(untitled) - Bodek, L.; Engelund, M.; Cebrat, A.; Such, B. (Beilstein J. Nanotechnol., 2020)

(untitled) - Bodek, L.; Cebrat, A.; Piatkowski, P.; Such, B. (J. Phys. Chem. C, 2019)

Molecular Magnets - Bartolomé, J.; Monton, C.; Schuller, I. K. (Magnetism of Metal Phthalocyanines, 2014)

(untitled) - Kolmer, M.; Godlewski, S.; Kawai, H.; Such, B.; Krok, F.; Saeys, M.; Joachim, C.; Szymonski, M. (Phys. Rev. B, 2012)

(untitled) - Godlewski, S.; Kolmer, M.; Lis, J.; Zuzak, R.; Such, B.; Gren, W.; Szymonski, M.; Kantorovich, L. (Phys. Rev. B, 2015)

(untitled) - Livadaru, L.; Pitters, J.; Taucer, M.; Wolkow, R. A. (Phys. Rev. B, 2011)

(untitled) - Engelund, M.; Godlewski, S.; Kolmer, M.; Zuzak, R.; Such, B.; Frederiksen, T.; Szymonski, M.; Sánchez-Portal, D. (Phys. Chem. Chem. Phys., 2016)

(untitled) - Godlewski, S.; Kolmer, M.; Engelund, M.; Kawai, H.; Zuzak, R.; Garcia-Lekue, A.; Saeys, M.; Echavarren, A. M.; Joachim, C.; Sanchez-Portal, D.; Szymonski, M. (Phys. Chem. Chem. Phys., 2016)

(untitled) - Huang, H.; Chen, W.; Chen, S.; Qi, D. C.; Gao, X. Y.; Wee, A. T. S. (Appl. Phys. Lett., 2009)

(untitled) - Godlewski, S.; Tekiel, A.; Prauzner-Bechcicki, J. S.; Budzioch, J.; Szymonski, M. (ChemPhysChem, 2010)

(untitled) - O'Rourke, J. K.; Brooks, J. S.; Bell, N. A.; Cawley, J.; Thorpe, S. C. (Sens. Actuators, B, 1993)